Agar-based ZIF-90 antibacterial hydrogels for biomedical applications. (26th July 2020) - Tian, Yong-Chang; Jiao, Cai-Cai; Wang, Song; Cong, Hai-Lin; Shen, You-Qing; Yu, Bing
Abstract: Bacterial infection is a major challenge for contemporary medicine, and antimicrobial hydrogels have been extensively studied for their excellent antimicrobial activity. However, the antibacterial agent also has high cytotoxicity and hemolytic activity while being significantly antibacterial. In this paper, we prepared a hydrogel by simple heating-cooling of ZIF-90 doped agar solution, which has obvious antibacterial activity against Gram-positive and Gram-negative bacteria. The test results show that the hydrogel has a uniform and stable structure and does not exhibit cytotoxicity and hemolytic activity while maintaining good bacteriostatic properties, so as to achieve the function of bacterial infection treatment and would healthcare.